2000
DOI: 10.4049/jimmunol.164.11.5641
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T Cell Responses to Self- and Mutated p53 Determinants During Tumorigenesis in Mice

Abstract: We analyzed CD4+ T helper responses to wild-type (wt) and mutated (mut) p53 protein in normal and tumor-bearing mice. In normal mice, we observed that although some self-p53 determinants induced negative selection of p53-reactive CD4+ T cells, other p53 determinants (cryptic) were immunogenic. Next, BALB/c mice were inoculated with J774 syngeneic tumor cell line expressing mut p53. BALB/c tumor-bearing mice mounted potent CD4+ T cell responses to two formerly cryptic peptides on self-p53. This response was cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…This response is mediated by T cells recognizing the mutated portion of p53 and by T cells directed to formerly cryptic self-p53 determinants. Interestingly, the anti-p53 Th response directed toward distinct p53 peptides depends upon the stage of tumorigenesis (31). In the present study, we demonstrated that the presence of p53-specific IgG antibodies correlates with the strong p53 staining intensity in the tumors of patients with primary colorectal cancer, although just a minority of the examined patients (39%) displayed a p53-specific humoral response.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This response is mediated by T cells recognizing the mutated portion of p53 and by T cells directed to formerly cryptic self-p53 determinants. Interestingly, the anti-p53 Th response directed toward distinct p53 peptides depends upon the stage of tumorigenesis (31). In the present study, we demonstrated that the presence of p53-specific IgG antibodies correlates with the strong p53 staining intensity in the tumors of patients with primary colorectal cancer, although just a minority of the examined patients (39%) displayed a p53-specific humoral response.…”
Section: Discussionmentioning
confidence: 67%
“…While these studies suggest that anti-p53 CD4 + T cells become activated during cancer, the nature of the p53 determinants recognized by these CD4 + T cells as well as the functional properties of these T cells are still unknown. It has been demonstrated that anti-p53 T cells specific to certain wild-type p53 determinants are present in the periphery of the adult immune system and can be specifically activated after p53 peptide immunization in tumor-bearing mice (31). More importantly, mice inoculated with syngeneic J774 metastatic sarcomas mount a potent CD4 + T-cell response to p53.…”
Section: Discussionmentioning
confidence: 98%
“…Infusion of epitope-pulsed DC requires mutation-specific or HLA haplotypespecific vaccination and would therefore have limited applicability. In addition, this immunization strategy might not stimulate responses to cryptic epitopes or stimulate a p53-specific Th response (43). To effectively target murine p53 in a syngeneic murine model, the viral immunization strategies previously used required either intratumoral injections or immunization before tumor challenge.…”
Section: Discussionmentioning
confidence: 99%
“…After two immunizations, the hTERT-specific CD4 ϩ T cell responses were 140 spots per 10 6 bulk splenocytes upon in vitro hTERT peptide restimulation in an IFN-␥ ELISPOT assay vs 10 spots per 10 6 bulk splenocytes in the absence of in vitro peptide restimulation. Similarly, high doses (50 g per mouse) of wild-type and mutant mouse p53 peptides in CFA were necessary for the induction of p53-specific CD4 ϩ T cell responses in naive mice (45). A second consequence of DEC205 targeting was that the immune T cells had a relatively good functional affinity.…”
Section: Evidence For Improved Cd4 ϩ T Cell Immunity To Survivin Follmentioning
confidence: 99%
“…In these studies, immunization required high doses of Ag and two or three injections to overcome tolerance and induce a CD4 ϩ T cell response (45,77). For example, HLA-DR4-transgenic mice had to be immunized twice with 100 g per injection of an MHC-II-restricted peptide from human telomerase reverse transcriptase (hTERT), emulsified in CFA, to detect hTERT-specific CD4 ϩ T cell responses (77).…”
Section: Evidence For Improved Cd4 ϩ T Cell Immunity To Survivin Follmentioning
confidence: 99%